Mindmeister’s Influence on 4C Skills in Indonesian Subject Grade 6 Elementary School in Surabaya - Yoedo, Yuli Christiana; Octaviani, Anita; Puspitasari, Dani (MO.RI Publishing, 2025)
This study aims to determine the influence of MindMeister on 4C skills in the Indonesian language subject in grade 6 elementary school in Surabaya. A combined research method was used, involving data collection carried out through in-depth interviews with students, observation, taking pre-test and post-test scores 3 times each in the control class and experimental class. Quantitative results showed no significant effect of using MindMeister on 4C skills (significance values of 0,100 > 0,05). However, the qualitative result based on the student's perspective gained through interviews and observations is that most students can apply 4C skills while using MindMeister. In conclusion, it is proposed that MindMeister may influence 4C skill levels in the Indonesian subject in this particular context. It is hoped that these findings contribute to the use of MindMeister in other subjects in any grade of elementary school in Indonesia.